A dyciandiamine-based methacrylate-epoxy dual-cure blend-system for stereolithography - Romeis, Manuel; Drummer, Dietmar (Polymers, 2021)
In this research, an epoxy-based dual-cure system is developed and characterized for SLA additive manufacturing. Dual-cure systems consist of UV-curable acrylates and thermal active components. The second curing step offers an additional degree of freedom to design specific material properties. In this study, a blend of varying concentrations of an epoxy/curing agent mix, respectively, DGEBA, DICY and photocurable methacrylate, was used to create a material that is printable in the SLA process into a UV-cured or green part and subsequently thermally cured to achieve superior thermal and mechanical properties. Calorimetric measurements were performed to determine the reactivity of the thermal reaction at different concentrations of epoxy. The fully cured specimens were tested in mechanical and dynamic mechanical measurements, and the results showed a significant improvement in tensile stress and glass transition temperature with rising epoxy concentrations. Fractured surfaces from tensile testing were investigated to further characterize the failure of tested samples, and thermal degradation was determined in TGA measurements, which showed no significant changes with an increasing epoxy concentration.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Additive manufacturing (AM); Dual-cure; Stereolithography (SLA)

Analysis of UV-Assisted direct ink writing rheological properties and curing degree - Jiang, Fengze; Wörz, Andreas; Romeis, Manuel; Drummer, Dietmar (Polymer Testing, 2022)
In this research, the relationship between the viscosity and curing degree of an acrylate-based resin under UV light was investigated by UV-rheometer and photo-DSC. The influences of different material compositions were studied with single-factor analysis. Viscosity and heat flow measurements were carried out to identify the relative states of the curing and to evaluate the material curing behavior by quantitative analysis. Different intensities were used to observe the effects on viscosity and curing degree. The findings of this work reveal the correlation between the relative curing degree and viscosity, which is divided into two parts depending on the light intensity. The correlated curve follows second-order polynomial under higher intensities, while the lower intensity follows a Gauss distribution. From the results, the relative curing degree is estimated by observing the viscosity of the resin system during the process. The critical curing degree was also determined to identify the resin phase transfer from the liquid to solid.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Additive manufacturing; Curing degree; Direct ink writing; Photopolymerization; Rheological properties

Investigation of the effects of energy density in Laser Sintering of polypropylene on morphological and dielectric properties for high-frequency antennas - Romeis, Manuel; Ehrngruber, Michael; Drummer, Dietmar (Procedia CIRP, 2024)
Advancements in the Internet of Things demand more capable antenna systems, which benefit from the complex geometries enabled by additive manufacturing. Novel approaches, such as external metallization of polymers, enable the design of these geometries but require the processing of low dielectric-loss polymers in additive manufacturing. Arising from prevailing limitations on additively manufactured low-loss components, this study investigates the effect of energy density on polypropylene's dielectric properties in powder bed fusion processes. Variations in laser power significantly influenced material density and mechanical characteristics. Both insufficient and excessive energy densities resulted in lower quality parts due to issues like fused particles or inadequate melting. Optimal dimensional accuracy and surface quality were achieved with energy levels slightly below those for peak density. While dielectric loss remained mostly stable, relative permittivity decreased at very low densities, where partial melting occurred. Relying on derived optimized parameters, the functionality of passive high-frequency components was demonstrated.
CRIS-Team Scopus Importer:2024-09-27
Keywords: high-frequency antenna; Laser Sintering (SLS); polypropylene

Laser-Sintering of Cyclic Olefine Copolymer for Low Dielectric Loss Applications - Romeis, Manuel; Ehrngruber, Michael; Drummer, Dietmar (Polymers, 2024)
With increasing demands for data transfer, the production of components with low dielectric loss is crucial for the development of advanced antennas, which are needed to meet the requirements of next-generation communication technologies. This study investigates the impact of a variation in energy density on the part properties of a low-loss cyclic olefin copolymer (COC) in the SLS process as a way to manufacture complex low-dielectric-loss structures. Through a systematic variation in the laser energy, its impact on the part density, geometric accuracy, surface quality, and dielectric properties of the fabricated parts is assessed. This study demonstrates notable improvements in material handling and the quality of the manufactured parts while also identifying areas for further enhancement, particularly in mitigating thermo-oxidative aging. This research not only underscores the potential of COC in the realm of additive manufacturing but also sets the stage for future studies aimed at optimizing process parameters and enhancing material formulations to overcome current limitations.
CRIS-Team Scopus Importer:2024-07-12
Keywords: additive manufacturing; COC; cyclic olefine copolymer; low dielectric loss; selective laser sintering; SLS

Neue Werkstoffe und Prozesse für die additive Fertigung - Drummer, Dietmar; Greiner, Sandra; Grützmacher, Constanze; Jiang, Fengze; Kleffel, Tobias; Romeis, Manuel; Schlicht, Samuel; Wolf, Michael (Jahresmagazin Ingenieurwissenschaften, 2022)
Keywords: Materialentwicklung; Dual-Core Systeme; SLA; Stereolithographie; UV-Assisted Direct Writing; Strangablegende AF; FFF; Fused Filament Fabrication; SLS; Niedertemperatur-Lasersinterprozess; Infrarotschweißen von SLS-Bauteilen

Prozessabhängigkeit der dielektrischen Eigenschaften im FFF von COC - Romeis, Manuel; Ehrngruber, Michael; Drummer, Dietmar (Tagungsband Technomer, 2023)
Das rasante Fortschreiten der technologischen Entwicklungen in Richtung Internet der Dinge erfordert den Austausch immer größerer Datenmengen, wodurch die Anforderungen an entsprechende Antennensysteme ebenfalls weiter wächst. Durch die komplexe Formgebung und die Eröffnung komplett neuer Geometriemöglichkeiten bieten sich Additive Fertigungsverfahren für die Herstellung solch innovativer Systeme natürlicherweise an. Eine Kombination aus einem Kunststoffgrundkörper und einer Metallisierung bietet hier eine Vielzahl von dielektrischen Eigenschaften und damit Anwendungsfeldern. Ein neuartiger Ansatz bevorzugt eine Außenmetallisierung gegenüber der klassischerweise eingesetzten Innenmetallisierung, um so die Geometrievielfalt nicht durch eine benötigte Zugänglichkeit der Innenstrukturen einzuschränken und so in innovativen und neuen Designs zu denken. Da allerdings in diesem Fall das elektromagnetische Feld durch den Kunststoff geleitet wird, müssen für diesen Prozess sehr verlustarme Kunststoffe für additive Fertigungsverfahren qualifiziert werden. Ein Kunststoff mit ausgezeichneten Voraussetzungen zur Erreichung dieser Zieleigenschaften ist COC. Eingesetzt wird im Rahmen dieser Untersuchung ein kommerzielles COC Filament der Firma CREAMELT und die Verarbeitung findet auf einer OpenSource FFF-Anlage der Firma Prusa statt. Im Rahmen der gezeigten Untersuchung findet eine Evaluierung der Prozess-Bauteileigenschafts-Zusammenhänge statt. Parameter, die dabei variiert werden, sind Verarbeitungstemperatur, Schichtdicke sowie Düsendurchmesser. Speziell die Variation des Düsendurchmessers ist hierbei ein wichtiger Aspekt um in die Abmessungen der angestrebten Antennenanwendung zu gelangen. Die Ergebnisse, die hierbei charakterisiert werden ist der Einfluss auf die Bauteilabmessungen, Oberflächenrauheit, Dichte sowie die dielektrischen Eigenschaften im Bereich 20 – 50 GHz mit Hilfe eines speziell für diesen Zweck angefertigten Messresonators. Ziel ist es daraus Fertigungsrichtlinien zur Erreichung der gewünschten Eigenschaften zu erstellen.Mit reduzierter Schichthöhe und Erhöhung der Temperatur findet eine bessere Einhaltung der Sollmaße statt. Die Änderung des Düsendurchmessers zeigt keinen Einfluss in der Untersuchung der Abmessungen, allerdings eine deutliche Verbesserung der Oberflächenqualität, die Dichte wiederum fällt mit der Reduktion des Düsendurchmessers geringer aus. Ein Einfluss der Schichthöhe konnte hier nicht gezeigt werden. Bei den Messungen der dielektrischen Eigenschaften konnte eine Reduktion der relativen Permittivität sowohl mit der Erhöhung des Düsendurchmessers sowie einer Erhöhung der Temperatur und Schichtdicke gezeigt werden. Der dielektrische Verlust zeigt ebenfalls eine Reduktion mit Zunahme des Düsendurchmessers. Ein Einfluss der Temperatur sowie der Schichthöhe konnte in den Untersuchungen nicht gezeigt werden. Durch eine Bewertung von dem Zusammenspiel aus Bauteilqualität und dielektrischen Eigenschaften können so optimierte Parameter für die Fertigung von Antennenarrays abgeleitet werde